PENGARUH DIMENSI SERVICE QUALITY TERHADAP CONSUMER SATISFACTION PADA LAYANAN DRIVE THRU - Putri, Rana Amira Nirmala; Radityo Putri Handrito (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
One of the company's strategies to survive during a pandemic and support this policy is to present a drive thru service system. many consumers are switching to alternative drive thru services to get products. For the company, customer satisfaction is one of the main keys to success. The objective of this research is to identify the effects of the dimensions of service quality on the satisfaction of drive thru service users in Malang city during the pandemic. This study is categorized as explanatory research since it explains the positions of tangibility, empathy, reliability, assurance, and responsiveness in affecting consumer satisfaction. Using purposive sampling with the criteria of individuals in Malang city with the minimum age of seventeen years who have used drive thru services during the pandemic, 364 people were selected as the sample. The results of the analysis performed in IBM Statistics SPSS 26 have led to findings that the five dimensions mentioned above are still applicable for the satisfaction of drive thru users in Malang city during the pandemic. Furthermore, tangibility and reliability are the only dimensions that are not relevant with consumer satisfaction in terms of drive thru service usage in Malang city during the pandemic.